2017
DOI: 10.1167/iovs.17-22989
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Derived Tryptase in Geographic Atrophy

Abstract: PurposeOur previous study demonstrated significantly more degranulating mast cells (MCs) in choroids from subjects with age-related macular degeneration compared to aged controls. This study examined the immunolocalization of tryptase, the most abundant MC secretory granule-derived serine protease, in aged control eyes and eyes with geographic atrophy (GA).MethodsPostmortem human eyes with and without GA were obtained from the National Disease Research Interchange. Tissue was fixed, cryopreserved, sectioned, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Interestingly, earlier reports of tryptase, another serine protease produced by mast cells in the choroid, has also been implicated in aging and the atrophic form of AMD leading to the GA in its late stage (29,37). While tryptase is associated with GA, our work demonstrated that GzmB is rarely present in GA eyes, but more significantly in CNV and soft drusen eyes ( Figures 2G,H, Supplementary Figure 6).…”
Section: Gzmb Immunoreactivity In the Outer Retinasupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, earlier reports of tryptase, another serine protease produced by mast cells in the choroid, has also been implicated in aging and the atrophic form of AMD leading to the GA in its late stage (29,37). While tryptase is associated with GA, our work demonstrated that GzmB is rarely present in GA eyes, but more significantly in CNV and soft drusen eyes ( Figures 2G,H, Supplementary Figure 6).…”
Section: Gzmb Immunoreactivity In the Outer Retinasupporting
confidence: 55%
“…It is hypothesized that the functional significance of GzmB cleavage of cell junctional proteins on RPE leads to the disruption of the blood-eye barrier, an early event in the pathogenesis of AMD (1,17,(29)(30)(31). We tested the barrier function of primary RPE cells grown on transwell inserts by measuring fluorescence associated with movement of FITC-labeled dextrans (70 kDa) across the RPE monolayer, an established method and indicator of solute flux used routinely to test barrier function of RPE (32)(33)(34).…”
Section: Extracellular Gzmb Causes Increased Dextran Flux In Confluenmentioning
confidence: 99%
“…Although mast cells are present in the choroid of humans and most vertebrates (May, 1999; McMenamin, 1997; McMenamin and Polla, 2013), their role in the eye in health and disease remains unknown. AMD is associated with an increased number of total and degranulated mast cells in the choroid (Bhutto et al, 2016; McLeod et al, 2017). However, the interpretation of these observations is unclear, as mast cells not only participate in proinflammatory responses but also can limit inflammation or facilitate its resolution (Caughey, 2011; Galli et al, 2008; Tsai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Similarly, increased numbers of activated choroidal macrophages and mast cells (MCs) are observed around atrophic lesions of human donor eyes, implicating complement-mediated MC degranulation. 11,12 Notwithstanding the idiosyncrasies of animal models not truly reflecting the human state, functional studies do indicate that the recruitment and accumulation of activated immune cells are critical for both neovascular and degenerative responses that characterize AMD. 5,[13][14][15][16][17] Non-resolving, persistent low-grade inflammation is a major drive of many chronic, age-related diseases, including metabolic disorders, neurodegenerative diseases, and cancer.…”
mentioning
confidence: 99%